2006
DOI: 10.1029/2005jb004031
|View full text |Cite
|
Sign up to set email alerts
|

Seismic wave attenuation in methane hydrate‐bearing sediments: Vertical seismic profiling data from the Nankai Trough exploratory well, offshore Tokai, central Japan

Abstract: [1] Data from two vertical seismic profiles (VSPs) from the Nankai Trough exploratory well, offshore Tokai, central Japan, are used to estimate compressional attenuation in methane hydrate (MH)-bearing sediments at seismic frequencies of 30-110 Hz. We compare spectral ratio and centroid frequency shift methods for measuring attenuation. To isolate intrinsic attenuation from total attenuation, attenuation is computed from multiples using one-dimensional synthetic VSP data from sonic and density logs. The use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 37 publications
6
39
1
Order By: Relevance
“…Given the two methodological approaches for estimating Q, their inherent limitations and the constraints of the 3D seismic, as earlier reported by Quan and Harris (1997) and Matsushima (2006), we also found that the centroid frequency shift method gave more stable Q estimates. The contribution of reflectivity sequences in the calculated amplitude spectrum and scattering effects limited the vertical resolution of Q estimates.…”
Section: Sa46 Interpretation / February 2016supporting
confidence: 81%
See 1 more Smart Citation
“…Given the two methodological approaches for estimating Q, their inherent limitations and the constraints of the 3D seismic, as earlier reported by Quan and Harris (1997) and Matsushima (2006), we also found that the centroid frequency shift method gave more stable Q estimates. The contribution of reflectivity sequences in the calculated amplitude spectrum and scattering effects limited the vertical resolution of Q estimates.…”
Section: Sa46 Interpretation / February 2016supporting
confidence: 81%
“…For example, studies on well-log data Goldberg, 2002, 2005;Matsushima, 2005), vertical seismic profile (VSP) data Bellefleur et al, 2007), and on crosshole seismic data (Pratt et al, 2003;Bauer et al, 2005) indicated an increase in attenuation. Other studies, mainly on surface seismic data (Matsushima, 2006;Rossi et al, 2007;Dewangan et al, 2014) indicated a decrease in attenuation. The increase (Guerin and Goldberg, 2002;Gei and Carcione, 2003;Chand and Minshull, 2004;Lee and Collett, 2006) and decrease (Sain and Singh, 2011;Dewangan et al, 2014) in attenuation have been explained by using different rockphysics models depending on the assumed microstructure of the hydrate and also sediment-hydrate mixtures.…”
Section: Introductionmentioning
confidence: 94%
“…It is consistent, however, with the positive correlation between increased hydrate content and higher Qp obtained at 'seismic' frequencies (30-110 Hz) from VSPs offshore Tokai, Japan (Matsushima, 2006). Consequently, it could be suggested that the attenuation mechanism of squirt-flow within the hydrate matrix proposed by or the combination of frictional and squirt-flow mechanisms proposed by Guerin and Goldberg (2005), both based on data from sonic logs, might not be expected to produce significant attenuation at lower, seismic frequencies This would be consistent with the attenuation model of Pride et al (2004), which predicts that squirt flow is only important at ultrasonic frequencies and that effects of mesoscale features, larger than pores but smaller than the seismic wavelength, govern attenuation at seismic frequencies.…”
Section: Inversion For Qp and Qs And The Effect Of Hydrate On Attenuasupporting
confidence: 81%
“…2(A)] and 83% of the P-wave velocity in the 43% saturation case. In contrast, the S-wave speed in hydrate-bearing sediment is expected to be less than $60% of the P-wave speed (Lee, 2002;Matsushima, 2006;Yun et al, 2005), even if the hydrate is cementing the sediment grains (Priest et al, 2005). Therefore, the large-amplitude arrival immediately following the P-wave is too fast to be an S-wave.…”
Section: B Sample Preparationmentioning
confidence: 98%